Informal Justice in England and Wales, 1760-1914 - Stephen Banks (Boydell Press, 2014)
This is a book about justice. It is not about justice as observed in the courtroom (unless it be a ‘courtroom’ of an unorthodox variety) but about unofficial justice as visited upon malefactors by the collective actions of private citizens. Justice is a difficult word, and I should say at the start that for my purposes the term ‘unofficial justice’ is taken to exclude deeds of furtive vengeance (however much deserved). I am not concerned here with those occasions upon which offenders were simply set upon in the dark and given a good beating – though it is likely that such instances occurred often enough. Rather my interest is in those occasions upon which groups acted openly, publicly and unapologetically against wrongdoers. Unapologetically because they claimed that they were doing so by right and in accordance with customary practices that supposedly legitimated group responses to moral defects. Reference will indeed be made to some actions that were both public and yet quite indiscriminate in respect of the violence visited upon the wrongdoer. However, it will soon become apparent that most public collective acts were intended primarily to shame their victims rather than to harm them, and that they were performed within an understood rubric of customary practice that served (in the main) to contain the violence inherent in group action. This study, then, is primarily focused on public shaming rituals – and these generally (though not invariably) involved a noisy perambulation through an offended community. During the course of these processions the participants tried to attract as much attention as possible by beating on pots, pans, kettles . . . anything suitable that came to hand. Hence these phenomena are broadly subsumed under the title ‘rough music’ – rituals that were widely distributed and known variously at the time as ‘skimmingtons’, ‘stang ridings’, ‘ceffyl prens’ and by many other terminologies besides.